Ecosystemic factors influencing the accessibility of ECD services for young children with disabilities in Zimbabwe - Steyn, Miemsie G. (University of Pretoria, 2018)
Young children with disabilities are often the most vulnerable members of developing countries, where they are marginalised and their rights often being overlooked. Thus, most young children with disabilities end up abandoned or neglected, with limited access to education. This study explores the ecosystemic factors that influence the accessibility of early childhood development services to young disabled children in Zimbabwe, focusing on the four- to five-year age group (referred to as “ECD B” in Zimbabwe). Grounded on Bronfenbrenner’s ecosystemic theory, the study adopted a qualitative approach and was situated in the interpretivist paradigm. The preference for the qualitative approach was to ensure that the researcher interacted with the people who were very close to children with disabilities and, henceforth, gather as much reliable and pertinent information as possible. The study was conducted with three special schools and an early childhood development centre, all located in the Bulawayo Metropolitan Province, following a multiple case study research design. To necessitate a high level of trustworthiness and comprehensive information, the data were gathered through interviews, focus group discussions and photovoice. Sources of rich information were purposively selected and comprised school principals of special schools, early childhood development teachers, officers of the Schools’ Psychological Services, health officers, parents and caregivers. The study establishes that although the government is mandated to provide services to its young population, challenges related to a lack of resources are inhibiting all its efforts. Despite the existence of stipulated national, regional and international agreements on the disposition of inclusivity, the research study established that the Zimbabwean education system has not yet been fully attuned to take aboard the needs of learners with diverse forms of disabilities. The education system lacks the commitment to enhancing the fulfilment of these learners’ rights towards this goal. The situation is exacerbated by the fact that school principals, early childhood development teachers and other stakeholders involved in the welfare of these children, are inadequately trained to handle young children with disabilities. Furthermore, schools face challenges on the scarcity of appropriate learning materials to support learners with disabilities, even though early childhood development is a crucial phase in the growth and development of young children with disabilities. Another constraining factor revealed, was negative social attitudes with deep roots in the cultural beliefs on causes of disability; these were found to be adversely influencing people’s reactions towards children with disabilities. The study concludes that young children with disabilities are not fully benefiting from the available early childhood development services and other educational programmes. The study, therefore, recommends that early childhood development teachers should receive a comprehensive teacher training programme that equips them with appropriate skills and empowers them with the knowledge to handle young children with disabilities. The study further recommends the implementation of inclusive policies to take aboard the needs of children with challenges and ensure their access to appropriate services and resources to mitigate their impediments.